Hegemoni Kekuasaan Melalui Motif Agama dan Sikap Nasionalisme: Analisis Semiotika Roland Barthes Terhadap Film Sang Kyai - Nurfiana, Efen (Fakultas Dakwah dan Komunikasi UIN Sunan Kalijaga, 2021)
AbstractIt cannot be denied that the failure of the people to carry out a revolution is caused by ideology, values, self-awareness and the people who are immersed in the hegemony of power. This hegemony can be formed through the massa media, sermons or preaching which indoctrination so as to give birth to a new ideology attached to the people. In the film Sang Kyai, the writer analyzes the hegemony of power that is inserted through religious motives and nationalistic attitudes. The author uses qualitative research with an interpretive type. The author uses the semiotic analysis method, referring to Roland Barthes' theory which draws on the principles of denotation, connotation and myth. The results of this study, as an application of the found denotation, the pesantren tradition. The withdrawal of the connotation of plague on elements of the pesantren tradition which is thick with the attitude of the santri ta'dzim towards the kiai and the kiai's role itself. The writer finds that the hegemony of power which is connected through religious channels will be able to be accepted openly and gently. In this regard, the author finds several hegemony of power that runs through religious motives in the film Sang Kyai, namely first, Seikerei's imposition of KH. Hasyim Asy'ari, when a kiai agrees to the Seikerei, the students and the people will agree to it. Second, KH. Hashim Asy'ari openly to emphasize power. Third, embracing the kiai in order to get the sympathy of students and the Indonesian people. Fourth, KH. Hasyim Asy'ari led Masyumi as well as Shumubu with the aim of instilling a trusting attitude towards Japan and as a Japanese effort to control the people's movements. Fifth, the power strategy formed through the conquest of NU ulama. Sixth, planting the multiplication of agricultural produce through Friday sermons in all mosques as well as streamlining the holy verses of the Koran and hadiths on this propoganda.The connotation of jihad in the pesantren tradition can be found through first, the struggle of the students in completing the country's independence. Second, deliberation. Third, ta'dzim santri to kiai for their efforts to free the kiai from Japanese hands. In this understanding, the myth of the film Sang Kyai can be drawn on the concept of power that is clustered through religious motives, that power in the name of religion becomes a legitimate power that can be exercised openly and accepted by the community.